Упростите выражение: 1) [latex] (x^{2} - 1)( \frac{1}{x-1} - \frac{1}{x+1} - 1) [/latex] 2) [latex](m+1+ \frac{1}{m-1}) : (m- \frac{ m^{2} }{m-1}) [/latex]

Упростите выражение: 1) [latex] (x^{2} - 1)( \frac{1}{x-1} - \frac{1}{x+1} - 1) [/latex] 2) [latex](m+1+ \frac{1}{m-1}) : (m- \frac{ m^{2} }{m-1}) [/latex]
Гость
Ответ(ы) на вопрос:
Гость
1) (x^2-1)([latex] \frac{1}{x-1} [/latex]-[latex] \frac{1}{x+1} [/latex]-1)=(x^2-1)([latex] \frac{x-1-(x-1)-(x^2-1)}{x^2-1} [/latex]=3-x^2 2) =[latex] \frac{m(m-1)+m-1+1}{m-1} [/latex]:[latex] \frac{m(m-1)-m^2}{m-1} [/latex]=[latex] \frac{m^2-m+m-1+1}{m^2-m-m^2} [/latex]=[latex] \frac{m^2}{-m} [/latex]=-m
Не нашли ответ?
Ответить на вопрос
Похожие вопросы